Os quatro elementos : terra, água, ar e fogo : um tetramorfo envolvido em um tênue limite entre o sagrado e profano - Rosinke, Patrícia (2019)
In this publication, there is a proposal to examine how much the boundaries between sacred and profane boundaries or between Religion and Science. A seemingly exotic situation: in the Roman Catholic Sinop Cathedral, 4 out of 7 panels (8 x 6.5 m) represent iconographic representations of four alchemical elements (water, air, fire and earth) to make the representation of the sacred marking not only the tetrogram of the four evangelists (Luke, Matthew, Mark, and John), located one on one of the four cardinal points, but also four Marian dogmas on one of these items presented as an iconic proposal of each of the four elements by a sacred artist. For the composition of this Thesis aims to bring something original, it is important to mention that it is common sense that a thesis is a collective construction involving the doctoral student and the advisor, thus, texts written by the advisor were incorporated into the Thesis. Thus, an assemblage was presented. The term 'assemblage' is French and was first brought by Jean Dubuffet in 1953 in a work of art where he made collages of three-dimensional materials, based on the principle that all material can be incorporated into a work of art. The research is qualitative and the data production instruments were semi-structured interviews and questionnaires. For the treatment of data for the analyzes, we opted for the data triangulation. According to Marcondes (2014), the triangulation for data analysis allows: data production, transcription of the surveyed data, a pre-analysis in which the data were worked through reflection, contextualization, exemplification, aiming to elucidate the research problem. Then, at the apex of the interpretation, a synthesis was constructed through the interaction between the research data, thus adopting a reflective behavior. The research has as subjects collaborating students of the course of Natural Sciences with qualification in Chemistry, of UFMT of Sinop / MT. In addition, the plastic and sacred artist Mari Bueno and the Historian Luiz Erardi were interviewed. As for the originality of the research, there was no academic production on the four elements in sacred spaces, nor any research on the panels of the cathedral of Sinop-MT. Considerations allow us to state that: the theme is important in the formation of science / chemistry teachers; According to the justifications, mainly because Science and Religion are ubiquitous in people's lives and because they consider the school a fundamental space in the formation of subjects, being the science classes motivating discussions about life and its phenomena. Thus, looking at the data produced allows us to infer that the present thesis is affirmative, that the boundaries between the sacred and the profane or between religion and science are very tenuous.